Effect of Preoxidant on The Changing of Low Molecular Weight of Natural Organic Matter - Hidayah, E. N.; A. T. Agripina; O. H. Cahyonugroho (Nusantara Science and Technology Proceedings)
Natural organic matter (NOM) is a complex organic compound that have been exist in water sources. The presence of NOM in water, especially the aromatic compound, could trigger the formation of disinfectant by-products (DBPs). Low molecular weight of NOM, one of the characterisctic of organic based on their molecular weight, is quite difficult to be removed in coagulation process. Preoxidation is one the effort to reduce carbon structure of organic matter and it has been known as pretreatment before coagulation process and advanced ones. The objective of this research is to track the changing of low molecular weight of NOM through preoxidation with pottasium permanganaate (KMnO4). Low molecular weight of NOM is presented by synapic acid. Detection of NOM properties was observed quantitatively by using total organic carbon (TOC) and qualitatively by using fourier transform infrared (FTIR). The results shown that KMnO4 could increase the concentration of TOC. According to FTIR analysis, the increasing of TOC concentration is proably due to the transformation of low organic matter into lower organic compound. FTIR showed the increasing of % transmitance of all functional groups of organic matter.